Probiotic Fermentation of Coconut Juice - Ajibola, O.O.; Lihan, S.; Awang Husaini, A.A.S.; Ngieng, N. S. (Borneo EkoSains and Universiti Putra Malaysia Sarawak Campus, 2019)
Over the last decade, coconut water has gained considerable attention due to its beneficial compound for health and sweet taste, beside its conventional applications in the beverage and Bio-pharmaceutical industries. Probiotic production of coconut is being considered as attractive novel probiotic beverage, which can provide both hydration and also beneficial compounds for health. In this study, the ultimate aim was to determine the growth, viability and fermentation of probiotic bacteria in pasteurized and unpasteurized coconut water. Lactococcus lactis-IO1 grew well in pasteurized and unpasteurized coconut juice and similar profile was observed. Higher cell viability of 109 CFU/mL was achieved from unpasteurized probiotic culture than pasteurized probiotic culture (108 CFU/ mL) after first 2 days production process at 30 °C and retained survivability at 4 °C with approximately 109-8 CFU/ ml after 28 days. Subsequent changes in the activities of pH, reducing sugar, total acidity and total soluble solid (Brix) between the pasteurized and unpasteurized coconut water were also monitored throughout the incubation period. Lactococcus lactis-IO1 has a faster reducing sugar uptake and increasing of pH, total acidity in unpasteurized coconut juice than pasteurized coconut juice during fermentation process. It can be concluded that Lactococcus lactis-IO1 in unpasteurized coconut juice can be used to produce a non-dairy functional juice with beneficial compounds for health, sport diet and beverage juice lover.